Broun, William. William Broun to Edwin Broun, Petersburg, VA, September 8, 1862. - Broun, William (Valdosta State University Archives and Special Collections, 2020., 1862)
Petersburg Sept 8th 1862 Dear Pa, I have just returned from Yellow Sulfur Springs with my health much improved and intend starting for my [Regiment] tomorrow (the 9th)
Letter from William Broun to his father Edwin Broun from Petersburg, Virginia, September 8, 1862. 2 pages on one sheet of paper.
Keywords: American Civil War (1861-1865); Broun, Edwin, 1819-1904; Broun, William, Captain, 1842-1908; Bull Run, 2nd Battle of (Virginia : 1862); Cedar Mountain, Battle of (Virginia : 1862); Hill, Ambrose Powell, 1785-1858; Jackson, Stonewall, 1824-1863; Longstreet, James, 1821-1904; Personal correspondence; Virginia--Montgomery County; Virginia--Northumberland County